Five- and 18-Year Outcome of Two Cases with Full-Arch Rehabilitations Ad modum All-on-4 in the Presence of Challenging Conditions - de Araújo Nobre, Miguel; Santos, Diogo; Ferro, Ana; Lopes, Armando; Antunes, Carolina Jorge; Vitor, Inês (European Journal of Dentistry, 2024)
Placing implants in fresh postextraction sites is a borderline rehabilitation procedure. The purpose of this report is to describe the pre-, per-, and postoperative procedures for maintaining long-term stability of two full-arch rehabilitations through the All-on-4 protocol, performed in the presence of challenging conditions. Two patients were referred for full-arch rehabilitation with immediate function, with both patients presenting infection in the jaws: patient 1 with an implant (position #45) inserted in a cystic cavity; patient 2 with one implant (position #24) inserted transsinus after the removal of a cyst on the base of the maxillary sinus and another implant (position #15) inserted with a dehiscence. Both patients received a preoperative dental hygiene appointment, a regenerative surgical protocol, and were enrolled in a postoperative maintenance protocol. After surgery a provisional prosthesis was provided ensuring immediate function, and 6 months after surgery, the final prosthesis was delivered. During the follow-up appointments (final follow-up at 5 and 18 years), the implants were stable, and no infection was observed for both patients. The present case report describes two full-arch rehabilitations in immediate function, supported by dental implants inserted in the presence of challenging conditions that do not represent the norm, rather are highly demanding for the clinical team, warranting caution in the interpretation of the results.
Keywords: dental implants; immediate function; full-arch; All-on-4; infection; dehiscence; cyst